Serological trail of Brucella infection in an urban slum population in Brazil - Martha Olivera Angel; Paula Ristow; Albert Icksang Ko; Cecilia Di–Lorenzo (Journal of Infection in Developing Countries)
Introduction: Brucellosis is a re-emerging zoonosis with new cases reported each year in many Latin American countries, but it is mostly under-recognized. This study presents a serological investigation of infection with Brucella abortus and Brucella canis in a poor urban community in the city of Salvador, Brazil.